Relasi PKB dan PDIP Pasca Konflik antara Bupati dan Wakil Bupati Bojonegoro - Seta Ubara Yusa Pratama; Aribowo (Universitas Airlangga, 2023)
This research focuses on the split in the PKB-PDIP coalition caused by the conflict between the Regent and Deputy Regent of Bojonegoro and examines the various factors causing the conflict. By reviewing how the PKB-PDIP coalition was formed, the coalition split, and the impact of the coalition split as a result of the conflict between the Regent and Deputy Regent of Bojonegoro. The results showed that the split between the PKB and PDIP coalitions was caused by a conflict between the Regent and Deputy Regent of Bojonegoro which started from a political agreement and the amount of power possessed by the Regent as a manifestation of power sharing after the candidacy process. There is a political agreement that was violated by the Deputy Regent and the amount of power that the Regent has to remove the Deputy Regent from government and the political sphere in Bojonegoro and strengthen the Regent's position as the number 1 person in Bojonegoro.